PROTOTIPE SISTEM AUTOBRAKE PADA MOBIL MENGGUNAKAN SENSOR JARAK ULTRASONIK HC-SR04 BERBASIS ARDUINO MEGA 2560 - Hidayanto, Ari; Winarno, Heru (Gema Teknologi, 2016)
Ari Hidayanto, Heru Winarno in this paper explain that The high number of traffic accidents is currently a factor in the driver's error in driving (human error). One of the accidents that often occur include car accidents. Of the several incidents that have occurred, the average accident occurred because of the driver's lack of concentration in driving his car. This resulted in the driver not being able to control the speed of the vehicle immediately when there was a sudden object in front, moreover this happened when the vehicle drove at high speed. To avoid this, when driving, it really needs a vehicle security system that also greatly affects the driver's safety. With the development of existing science and technology allows humans to make security systems in motorized vehicles. Accidents due to driver negligence can be overcome by making the braking system automatic then the vehicle speed will slow down and carry out mechanical braking (disc brake) automatically based on the minimum distance of the car with the barrier even though the driver does not pull the brake lever. Realizing this, an autobrake system (automatic braking) was designed based on the distance of the car with the barrier using the HC-SR04 ultrasonic distance sensor. When between a sensor and a barrier at a distance of <= 70 cm, the central lock actuator will go forward and press the disc brake lever. System notifications will be displayed via 20X4 LCD, LED and Buzzer. The system work will be controlled by Arduino Mega 2560. Keywords: Autobrake, Disc Brake, Ultrasonic sensor HC-SR04, Central Lock, LCD 20x4, Arduino Mega 2560ReferencesAgus Setya Abadi, Delta. 2008. Sensor Ultrasonic Sebagai Alat Navigasi Robot Pemadam Api. Tugas Akhir PSD III Teknik Elektro (tidak diterbitkan). Semarang: Universitas Diponegoro.Bishop, Owen. 2004. Dasar-Dasar Elekrtonika. Jakarta: Penerbit Erlangga.Cahyo Saputro, Adi. 2014. Central Door Lock. Diunduh dari http://otomotifmaju.blogspot.com/2014/08/sentral-door-lock.html, pada 17 Juni 2015 pukul 21.46 WIB.Chan, Yefri. 2010. Teori Dasar Rem. Buku Panduan Teknik Mesin (tidak diterbitkan). Jakarta Timur: Universitas Darma Persada.Putu Giovani. I. 2014. Merancang Driver Motor DC. Diunduh dari http://www.geyosoft.com/2014/merancang-driver-motor-dc, pada 17 Juni 2015 pukul 08.00 WIB.Prayogo, Rudito. 2012. Pengaturan PWM dengan PLC. Tugas Mata Kuliah Teknik Otomasi (tidak diterbitkan). Malang: Universitas Brawijaya.Roghib, Rokhman, dan M. Qomarruzzaman. 2014. Introduction Arduino Training Kit. Yogyakarta: House Of Technology.Sandi. 2014. Acccumulator Atau Aki. Diunduh dari http://www.sandielektronik.com/2014/03/accumulator-atau-aki.html, pada 30 Mei 2015 pukul 16.15 WIB.Setyadi, Ary. 2010. Bahasa Indonesia Dalam Karya Ilmiah. Semarang: Fakultas Ilmu Budaya Undip.Sulistyowati, Riny. 2012. Perancangan Prototype System Kontrol Dan Monitoring Pembatas Daya Listrik Berbasis Mikrokontroler. Tugas Akhir Teknik Elektro (tidak diterbitkan). Surabaya: Institut Adhi Tama Surabaya.Tooley, Mike. 2003. Rangkainan Elektronik Prinsip dan Aplikasi Edisi Kedua. Jakarta: Penerbit Erlangga.